Effect of natural hazards on the household financial asset allocation: Empirical analysis based on CHFS2019 data - Liu, Tingyi; Li, Jie; Li, Dongju (Frontiers in Environmental Science, 2022)
Natural hazards are a common challenge to human survival and development. China is a country that is prone to natural hazards because of its vast territory and vast area. In fact, China is one of the countries most affected by natural hazards. The impact of natural hazards is often multidimensional, and the occurrence of natural hazards can have a dramatic impact on government finances and household property structures. However, existing research in China has mainly focused on individual factors and the household level, and there are gaps in the impact of natural hazards on the economic status of households. Based on the China Household Finance Survey-2019(CHFS) data, this paper investigates the impact of natural hazards on household financial asset allocation using the Probit and Tobit models and the propensity score matching method. It is found that: the occurrence of natural hazards significantly reduces the likelihood of households' investment in stocks and risky assets; older, more economically advanced and better educated household heads are more willing to make risky investments; and households with lower financial literacy are more affected by natural hazards in terms of investment in risky financial assets than those with high financial literacy. Therefore, it is necessary for the government to do pre-disaster prevention and post-disaster reconstruction, and further improve the social security mechanism and optimize the risk management system, so that more households can participate in the financial market and thus obtain higher investment returns.